Paradoxes of ayahuasca expansion: the UDV-DEA agreement and the limits of freedom of religion - Labate, Beatriz Caiuby (Drugs, 2012)
This article comments on the agreement signed in 2010 between a US branch of the Brazilian ayahuasca religion União do Vegetal (UDV) and the US Drug Enforcement Agency. This document settles a dispute regarding administrative issues involving ayahuasca, a psychoactive brew used by this group as a religious sacrament. The government originally confiscated this substance in 1999, and the matter went to the Supreme Court, which handed down a decision favourable to the UDV in 2006. Despite the fact that this group prevailed, the agreement reveals that the Drug Enforcement Agency (DEA) views ayahuasca not as a religious sacrament, but as a toxic and hazardous compound. This article also contextualizes this agreement in relation to the history of the UDV, which has been expanding beyond the Amazon since the 1970s. This process entailed increasing levels of institutionalization, formalization and bureaucratization. In its search for social legitimacy and legal conformity, the group has gradually shifted from its popular Amazonian origins. This process reached its peak with the current agreement with the DEA. Nevertheless, the agreement surpassed the levels of control and interference that would be tolerated by these religions in Brazil. It raises serious concerns for all those interested in human rights, religious freedom and cognitive liberty.
Published online: 25 Aug 2011
Gesehen am 30.10.2018